Discrimination of reconstituted milk from fresh skim milk by using lactulose and furosine as milk quality indicators - Jou-Hsuan Ho; Ming-Yu Chou; Yung-Jia Chan; Chi-Fa Chow; Tan-Ang Lee; Wen-Chien Lu; Ming-Fu Wang; Po-Hsien Li (Journal of Agriculture and Food Research)
This study aims to develop a novel and rapid method which uses enzymatic spectrophotometric assay and high-performance liquid chromatography (HPLC) for differentiating adulterated milk from pure fresh milk. Furthermore, this study will use the lactulose and Maillard-derived compounds as indicators to distinguish reconstituted milk from fresh milk. In bottle-sterilized milk, lactulose concentration decreased with the increasing addition of reconstituted skim milk. In addition, the content of lactulose in raw, low-temperature long-time (LTLT), and high-temperature short-time (HTST) skim milk samples increased with the proportion of reconstituted milk. Furosine, which had a retention time (RT) of 4.686 min in standard solution, had the RTs of 4.908, 4.926, 4.940, and 4.973 min in raw, LTLT, HTST, and bottle-sterilized milk samples, respectively. The RT peak increased along with the content of reconstituted milk in raw, LTLT, and HTST milk samples but decreased in bottle-sterilized milk. In conclusion, this work represents an important step toward detecting adulterated milk and tightening food safety regulations.